2015
DOI: 10.1002/jcb.25462
|View full text |Cite
|
Sign up to set email alerts
|

Combinatorial PX‐866 and Raloxifene Decrease Rb Phosphorylation, Cyclin E2 Transcription, and Proliferation of MCF‐7 Breast Cancer Cells

Abstract: As a potential means to reduce proliferation of breast cancer cells, a multiple-pathway approach with no effect on control cells was explored. The human interactome being constructed by the Center for Cancer Systems Biology will prove indispensable to understanding composite effects of multiple pathways, but its discovered protein–protein interactions require characterization. Accordingly, we explored the effects of regulators of one protein on downstream targets of the other protein. MCF-7 estrogen receptor-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Recently, a similar phenomenon was reported in MCF‐7 human breast cancer cells. In MCF‐7, combination therapy with a PI‐3‐kinase inhibitor and a selective oestrogen receptor modulator caused a large decrease in CCNE2 mRNA but very little change in cyclin E2 protein abundance …”
Section: Discussionmentioning
confidence: 99%
“…Recently, a similar phenomenon was reported in MCF‐7 human breast cancer cells. In MCF‐7, combination therapy with a PI‐3‐kinase inhibitor and a selective oestrogen receptor modulator caused a large decrease in CCNE2 mRNA but very little change in cyclin E2 protein abundance …”
Section: Discussionmentioning
confidence: 99%
“…We previously reported the highly significant decrease of proliferation of MCF-7 cells after three days of treatment with 1.0 μM raloxifene alone or in combination with 0.1, 0.4 or 0.8 μM PX-866 and the absence of any significant decrease of MCF10A cell proliferation following identical treatment [57]. As documented, there are few cellular or intracellular functions even remotely related to cell division, growth or cancer that are hTERT-independent, and this includes gene expression, signaling, survival, mitochondrial function and migration [9].…”
Section: Discussionmentioning
confidence: 99%
“…We previously reported that IL-11 transcription was significantly decreased by raloxifene in combination with PX-866 in MCF-7 cells [57]. Recognized contributions of IL-11 to cancer include development, apoptosis evasion, angiogenesis, progression and metastasis in multiple cancer cell types [67].…”
Section: Discussionmentioning
confidence: 99%
“…As a result, the therapeutic potential of these combination therapies is restricted 59–62 . When raloxifene and sonolisib are combined, the expansion of breast cancer cells is significantly reduced, proving that the combination therapy has certain potential for patients with breast cancer 63 . In recent studies, sonolisib has been shown to inhibit temozolomide-induced autophagy and promote apoptosis in GBM cells, thereby enhancing antitumor efficacy.…”
Section: Pi3k Inhibitorsmentioning
confidence: 99%